A new species of Harttia from the rio São Francisco basin (Siluriformes: Loricariidae) - Caldas, Laís [UNESP]; Cherobim, Arieli Matheus [UNESP]; Langeani, Francisco [UNESP] (FapUNIFESP (SciELO), 2022)
The genus Harttia belongs to the subfamily Loricariinae and has to date 27 described species, distributed in the drainages of Guiana Shield, Amazon and southeastern Brazil. The new species is distinguished from its congeners by the combination of: canal plate present; abdominal plates absent; trapezoid preanal plates; males with elongated and conspicuous odontodes on the first pectoral-fin ray and on the lateral region of the head, close to the canal plate; and dorsal-fin spinelet present. An identification key for the species of the rio São Francisco basin and a comparison between the new taxon and all other species of the genus are presented.
Keywords: Brazilian Crystalline Shield; Brazilian Plateau; Identification key; Streams; Waterfalls